How Can We Measure Progress on Social Justice in Health Care? The Case of Egypt. Issue 1 (2nd January 2017) - Pande, Aaka; El Shalakani, Amr; Hamed, Alaa
Abstract : Abstract —Social justice, broadly defined as providing equal access to liberties, rights, and opportunities especially for the least advantaged members of society, is a priority of several governments in the Middle East and North Africa (MENA) post−Arab Spring as well as globally. Achieving social justice in the field of health care is consistent with the principles of universal health coverage and is an important means to achieve this aim. To translate this abstract concept into concrete action, we propose a novel diagnostic method and then apply it to the case of Egypt, a country with a stated goal of achieving social justice in health care. This allows us to assess progress and then suggest targeted recommendations through which to improve social justice in health care. Through a comprehensive analysis of primary and secondary qualitative and quantitative data sources, we first identify six disadvantaged groups in Egypt and then analyze the status of these groups with respect to the three objectives of a health system—improving health outcomes, financial protection, and public satisfaction. Our results suggest that Egypt faces 11 challenges to achieving social justice in health care that can be addressed through 14 short- and medium-term recommendations drawn from global evidence of what works. Implementing these health system changes can help advance social justice in health care in Egypt.